2020
DOI: 10.3390/s20174804
|View full text |Cite
|
Sign up to set email alerts
|

Design of a High Precision Ultrasonic Gas Flowmeter

Abstract: Aiming at the problems of substantial pressure loss, small range ratio and contact measurement in traditional gas flowmeters, this paper designs a new type of data-filtering ultrasonic gas flowmeter. The flowmeter is composed of hardware circuits such as STM32F407 (ARM Cortex 32-bit microcontroller) main control chip and high-precision timing chip TDC-GP22 (time to digital converter). The software uses a new data-filtering algorithm combining Kalman filtering algorithm and arithmetic average algorithm to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Robot. e mobile sentry robot platform using an STM32F407 processor can detect flames through an infrared thermal imager and realize the functions of patrol, self-identification of flames, confirmation of fire size, and alarm or extinguishing [24]. e robot can move freely within a specific range, patrol automatically, detect obstacles through ultrasonic sensors, and turn automatically when the distance is shorter than the set value.…”
Section: Construction Of Mobile Sentrymentioning
confidence: 99%
“…Robot. e mobile sentry robot platform using an STM32F407 processor can detect flames through an infrared thermal imager and realize the functions of patrol, self-identification of flames, confirmation of fire size, and alarm or extinguishing [24]. e robot can move freely within a specific range, patrol automatically, detect obstacles through ultrasonic sensors, and turn automatically when the distance is shorter than the set value.…”
Section: Construction Of Mobile Sentrymentioning
confidence: 99%
“…Moreover, the signal processing technology and methods required to achieve relatively accurate measurements through effective processing and modification of ultrasonic signals under complex flow field have been researched extensively. 5,6 For example, a new signal processing method was proposed to determine the transit time difference, particularly at lower signal-to-noise ratios, and to improve the accuracy of transit time difference estimations using clamp-on time-of-flight ultrasonic flow meters for wet stream flows. 7 A method of modeling the received ultrasonic signal using variable frequency analysis was also proposed and validated for an ultrasonic gas flow meter.…”
Section: Introductionmentioning
confidence: 99%
“…The study of this scientific direction showed that the reactive properties and negative differential resistance are inextricably linked, and the multifunctionality and simplicity of radiomeasuring devices based on transistor structures with negative differential resistance is a promising direction in their construction and practical use. Also, the application of the principle of conversion "gas flow ratefrequency" based on transistor structures with negative differential resistance significantly reduces the cost of infocommunication-measuring devices and systems, and also allows to reduce the mass-dimensional characteristics of radio measuring gas flow transducers, to increase not only sensitivity, but also accuracy converting an informative signal to frequency [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%